Adsorption behavior of 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin on pristine and doped black phosphorene: A DFT study. (October 2017) - Zhang, Hong-ping; Hou, Jia-liang; Wang, Yaobin; Tang, Ping-ping; Zhang, Ya-ping; Lin, Xiao-yan; Liu, Changsheng; Tang, Youhong
Abstract: Polychlorinated dibenzo-p-dioxins (PCDDs) are highly toxic to humans. The search for novel and effective methods and materials for detecting or removing these gas pollutants is becoming more important and urgent. With its high specific surface area, abundance, and variety of potential applications, phosphorene has attracted much research interest. In this study, density functional theory was used to study the interactions between a doped phosphorene sheet and a tetrachlorodibenzo-p-dioxin (TCDD) molecule. The initial configurations of the TCDD and metallic (Ca or Ti) or nonmetallic (S and Se) dopants were investigated during the TCDD–phosphorene interaction study. Adsorption energy, isosurface of electron density difference, and density of states analysis were utilized to explore the interactions between TCDD and phosphorene. The results indicated that Ca dopant effectively improved the interaction between TCDD and phosphorene. Se dopant reduced the interaction between TCDD and phosphorene. Combining interactions between TCDD and the pristine, Ca-doped, and Se-doped phosphorenes, phosphorene could be a promising candidate for TCDD sensing and removal. Highlights: Pristine phosphorene exhibits outstanding capture ability for TCDD than pristine graphene and BN nanotubes. Ca-doping could improve the TCDD capture ability of phosphorene while Se doping would reduce the ability. Phosphorene based materials are expected to be potential materials for TCDD detecting or removing.